2014
DOI: 10.1039/c4sm00213j
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emulsification in ionic liquid/water systems and its use for templating of solids

Abstract: We report on the spontaneous formation of nano-sized ionic liquid/water (IL/W) emulsions in a simple system solely composed of an IL and aqueous solution of an inorganic salt. The IL ions play a dual role, that of both a surfactant and the dispersed phase. No extra surfactant is needed to promote emulsification. Droplets generation at the IL/W interface is captured by nanoparticulate and porous films that imprint the morphology of this unstable interface. The emulsion droplets are employed to create core-shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…On the other hand, components of predominantly hydrophobic character can be solubilized in water with the aid of emulsions that can contain ILs as a dispersed phase [11,-12]. Yet, unless spontaneously created at specific conditions [13], the emulsion formulation usually requires application of high mechanical force and high concentration of stabilizing agents. Stabilizing agents hinder direct contact of the dispersed and dispersing phase.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, components of predominantly hydrophobic character can be solubilized in water with the aid of emulsions that can contain ILs as a dispersed phase [11,-12]. Yet, unless spontaneously created at specific conditions [13], the emulsion formulation usually requires application of high mechanical force and high concentration of stabilizing agents. Stabilizing agents hinder direct contact of the dispersed and dispersing phase.…”
Section: Introductionmentioning
confidence: 99%
“…A diverse variety of emerging applications of ILs in the field of microfluidics and optics have been witnessed over the past years, such as analytes extraction [24][25][26], new emulsion formation [27], and electro-optical modulation [28,29]. Chen, et al presented a localization of dyes at the water/IL interface and the absorption of dye into the IL phase through a sandwich liquidcore waveguide, which could be beneficial for monitoring dynamic extraction processes in biological research [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wijethunga, et al demonstrated drop-to-drop liquid-liquid microextraction based on electrowetting on dielectric (EWOD) digital microfluidic chip [26]. Kowacz, et al reported that the spontaneous formation of nano-sized ionic liquid/water (IL/W) emulsion, providing a potential method for creating functional core-shell microcrystals [27]. Souza, et al studied the optical nonlinearity of ILs and showed that the nonlinear refractive index and thermo-optical coefficient dispersion are determined by the anions of ILs, promoting the engineering of ILs to aim at optical nonlinear applications [30].…”
Section: Introductionmentioning
confidence: 99%
“…40−42 We subsequently developed this liquid/liquid interface adsorption and self-assembly method to fabricate microstructures of the amphiphilic block copolymer polystyrene-b-poly(acrylic acid)-b-polystyrene (PS-b-PAA-b-PS) with metal ions by using a mixed DMF/CHCl 3 solution as the organic phase instead of a CHCl 3 solution. 45,46 The polymer molecules and metal ions adsorbed around the emulsion droplets and coordinated with each other, after which the fabricated emulsion droplets adsorbed and accumulated at the planar liquid/liquid interface, by further assembling into composite thin films with foam structures. 45,46 The polymer molecules and metal ions adsorbed around the emulsion droplets and coordinated with each other, after which the fabricated emulsion droplets adsorbed and accumulated at the planar liquid/liquid interface, by further assembling into composite thin films with foam structures.…”
Section: Introductionmentioning
confidence: 99%